KARTINI: PERJUANGAN DAN PEMIKIRANNYA - Sudrajat - Sudrajat (Mozaik: Kajian Ilmu Sejarah, 2007)
Abstract Kartini was native Indonesian woman in that have consciousness gender equality. Despite as a woman’s hero, Kartini has a perpective about the way   how to reach for Indonesian independent. All about of the Kartini perspectives was writeen on his letters that send to his friends. Later, JH Abendanon collects Kartini’s letters and published it on the title Door Duisternis Tot Licht (Out of Dark Comes Light). This article attemp to analizes the struggle and views of Kartini. The writers recite her letters in which publishes by Agnes Symmer by the title of Letters of A Javanese Princess: Raden Adjeng Kartini. By employing critic-analytical method the writers attempt to compare this book with another. The struggle of Kartini includes a gender equality, because she attemps to increase the degree of Indonesian woman by empowering themselves.  Kartini says that Indonesian woman must be out from handcuff customs. It can be reach with education in which employee the Indonesian woman.  Kartini wanted native Indonesian women have the freedom to learn and study. Kartini so has a perspective  about the way that can be reach to Indonesian independent with  nationalism, unity and social solidarity. The nationalism that Kartini’s views, includes the universal nationalism.  It means that the idea of kartini nationalism appears universal moral value: liberty, equality, solidarity, and fraternity.